Someone Writes About Cinema. The Reader's Columns on the Communist Magazines Vie Nuove, Il Calendario del Popolo and Rinascita from 1945 to 1960 - Marco Zilioli (Cinergie, 2019)
In 1953 Aldo D’Alfonso edited the volume Mille domande a Vie Nuove. Mille risposte a Vie Nuove, the first collection of letters published in the Communist magazine Vie Nuove concerning the column dedicated to the correspondence, that so called Corrispondenza con i lettori. Taking this seminal work as a starting point, I will focus on studying the correspondence within the Communist periodicals in the second post-war period. In order to achieve this purpose in a more extensive and complete way, I will also examine the letters published in two other periodicals of the same period – Rinascita and Il Calendario del Popolo – taking into account those letters specifically dedicated – in various ways – to cinema. In particular, I will analyze the topics of these letters dealing with the relationship between cinema and readers in non-film specific cultural magazines, with the aim to provide a picture of how people experienced and perceived cinema and, analyzing the geographical origin and the age of the letters writers, to trace out a profile of the readers.